PENGARUH DIGITAL MARKETING TERHADAP KEPUTUSAN PEMBELIAN : PERAN MEDIASI DARI PERILAKU KONSUMEN - Alamsyah, Nur Arya; Fikri, Muhammad Ali (Universitas Muhammadiyah Gresik, 2024)
This research investigates the impact of digital marketing on purchasing decisions, with consumer behavior as a mediating variable. The study focuses on active social media users in Indonesia, particularly in the Special Region of Yogyakarta. Adhering to established sampling guidelines, the sample size ranges from 30 to 500 respondents. Data collection utilized online questionnaires disseminated via social media platforms. Findings indicate significant relationships between digital marketing and purchasing decisions, digital marketing and consumer behavior, and consumer behavior and digital marketing. Furthermore, consumer behavior mediates the relationship between digital marketing and purchasing decisions. The study also confirms a relationship among consumer behavior, digital marketing, and purchasing decisions.